On Anti-Periodic Solutions for a Class of Impulsive Retarded Functional Differential Equations - Afonso, S. M. [UNESP]; Furtado, A. L. (Springer Nature, 2017)
In this paper, some new results on the existence and uniqueness of anti-periodic solution for a first-order impulsive functional differential equation with delay are obtained. The main tool to be employed here is the coincidence degree theory.
Keywords: anti-periodic solution; coincidence degree; Existence and uniqueness; impulsive retarded differential equations